ChemInform Abstract: Suzuki Coupling Based Synthesis and in vitro Cytotoxic Evaluation of 7‐Heteroaryl‐Substituted Camptothecin Analogues. Issue 33 (19th August 2014) - Wang, Lei; Huang, Ying; Zhang, Jie; Tong, Linjiang; Chen, Yi; Lu, Wei; Huang, Qingqing
Abstract All of the new compounds (IV) show potent inhibition of human tumor cell growth.